Effects of nanosilicate functionalized polycaprolactone membrane on bone mesenchymal stem cells-induced bone repairing - XIAO Long, HU Weiqiang, LIN Xuxin, HE Mengjiao, LUO Kai, XU Xiongcheng (Kouqiang yixue)
Objective To fabricate nanosilicate functionalized polycaprolactone (PCL/LAP) electrospun membrane and evaluate its role in bone marrow mesenchymal stem cells (BMSCs)-induced bone repairing. Methods The PCL/LAP electrospun membranes were fabricated via electrospinning technology and co-cultured with rat BMSCs. The cytocompatibility of the membranes was evaluated through cytoskeleton staining, live/dead cell staining and CCK-8 assay. The migration capacity of BMSCs was assessed using scratch assay, Transwell migration experiments and expression of migration-related genes (Pdgf and Tgfβ) was evaluated by qRT-PCR. The osteogenic differentiation and pro-angiogenesis potential were determined by alkaline phosphatase (ALP) staining, alizarin red staining, expression levels of osteogenesis-related genes (Alp, Col1a1, Runx2, Bglap and Bmp2) and angiogenesis-related genes (Angpt1, Fgf2 and Vegfa) along with RUNX2 protein expression. PCL and PCL/LAP electrospun membranes conditioned medium was subsequently used to stimulate vascular endothelial cells (EAhy926). The expression of angiogenesis-associated genes (KDR, ENOS and HIF1A) was quantified by qRT-PCR. Results BMSCs adhered well to the surface of the PCL/LAP membranes, with no significant impact on cell viability (P>0.05). PCL/LAP membranes not only promoted the proliferation (P<0.05), migration (P<0.05), but also enhanced ALP activity and mineralized nodule formation (P<0.05), increased osteogenic differentiation gene and protein expression (P<0.05) of BMSCs. Moreover, PCL/LAP promoted the expression of angiogenic genes of BMSCs (P<0.05), to indirectly regulate angiogenesis-related gene expression in vascular endothelial cells (P<0.05). Conclusion PCL/LAP electrospun membranes exhibit excellent biocompatibility and can promote proliferation, migration, osteogenic differentiation and BMSC-mediated angiogenic differentiation, showing great potential for bone defect repairing as barrier membrane.